2000
DOI: 10.1289/ehp.0010829
|View full text |Cite
|
Sign up to set email alerts
|

Low-level exposure to methylmercury modifies muscarinic cholinergic receptor binding characteristics in rat brain and lymphocytes: physiologic implications and new opportunities in biologic monitoring.

Abstract: Methylmercury (MeHg) affects several parameters of cholinergic function. These alterations are thought to play a role in MeHg neurotoxicity. In vitro experiments have indicated that MeHg acts as a strong competitive inhibitor of radioligand binding to muscarinic cholinergic receptors (mAChRs) in rat brain. Furthermore, rat brain mAChRs share several pharmacologic characteristics of similar receptors present on lymphocytes. Using the muscarinic antagonist [(3)H]quinuclidinyl benzilate (QNB) to label receptors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…For example, cerebral and lymphocyte mAChR binding was similarly modified by treatments with cholinergic agonist or antagonist drugs (Costa et al 1990) as well as by MeHg (Coccini et al 2000) and organophosphorus insecticides (Fitzgerald & Costa 1993). Changes in mAChRs were also observed in developing rats exposed perinatally to MeHg (Coccini et al 2007a) or to mixtures of MeHg and PCBs (Coccini et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, cerebral and lymphocyte mAChR binding was similarly modified by treatments with cholinergic agonist or antagonist drugs (Costa et al 1990) as well as by MeHg (Coccini et al 2000) and organophosphorus insecticides (Fitzgerald & Costa 1993). Changes in mAChRs were also observed in developing rats exposed perinatally to MeHg (Coccini et al 2007a) or to mixtures of MeHg and PCBs (Coccini et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have indicated that MeHg acts as a strong competitive inhibitor of radioligand binding to mAChRs in the rat (Castoldi et al 1996) and human brain tissue (Basu et al 2005). Brain mAChRs share several pharmacological characteristics of similar receptors present on lymphocytes and parallel changes in the density of mAChRs have been shown to occur in lymphocytes and brain tissue following exposure to pharmacological agents and neurotoxicant chemicals acting at the cholinergic system (Coccini et al 2000, Costa et al 1990, Fitzgerald & Costa 1993). MeHg was shown to alter cerebral mAChR density both in brain and lymphocytes following repeated oral administration to adult rats with changes in peripheral mAChR binding even preceding those observed in brain (Coccini et al 2000, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylmercury has been shown to affect neurochemical parameters in the brain: rats exposed to MeHg showed decreased monoamine oxidase (MAO) activity [35], decreased acetylcholinesterase (AChE) activity [36], and increased muscarinic acetylcholine receptor (mAChR) density [37]. Acetylcholine (ACh), a major neurotransmitter in the central nervous system, binds nicotinic ACh receptors (nAChRs) and mAChRs [38].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the α4-subunit gene (CHRNA4) or the β-subunit of the neuronal nicotinic acetylcholine receptor (nAChR) are associated with autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE), a focal syndrome characterized by nocturnal motor seizures (for review, see Lerche et al, 2001; Graves, 2006). MeHg has the potential to affect both nicotinic (Shamoo et al, 1976; Eldefrawi et al, 1977) and muscarinic receptors (Abd-Elfattah and Shamoo, 1981; Castodi et al, 1996; Coccini et al, 2000; Limke et al, 2004a; Roda et al, 2008). However, whether these effects of MeHg on nicotinic or muscarinic receptors lead to increased or decreased excitability remains to be determined.…”
Section: Introductionmentioning
confidence: 99%